2016
DOI: 10.1016/j.cellsig.2016.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of the FOXO3a transcription factor by mTORC2 induces a pro-survival response following exposure to ultraviolet-B irradiation

Abstract: Exposure to ultraviolet-B (UVB) irradiation, the principal cause of non-melanoma skin cancer (NMSC), activates both the rapamycin-sensitive mammalian target of rapamycin complex 1 (mTORC1) and the rapamycin-resistant mTORC2. We have previously reported that UVB-induced keratinocyte survival is dependent on mTORC2, though the specific mechanism is not well understood. FOXO3a is an important transcription factor involved in regulating cell survival. The activity of FOXO3a is reduced as a result of protein kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 81 publications
2
32
0
Order By: Relevance
“…As mentioned above, activation of various signaling pathways in the skin can occur as quickly as 5 minutes following exposure to UVR with peak activity occurring between 30 minutes to 1 hour on average [127129]. The RTKs belong to an important family of receptors that are rapidly activated in response to UVR and have been linked to NMSC [24, 130, 131].…”
Section: Rtk Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, activation of various signaling pathways in the skin can occur as quickly as 5 minutes following exposure to UVR with peak activity occurring between 30 minutes to 1 hour on average [127129]. The RTKs belong to an important family of receptors that are rapidly activated in response to UVR and have been linked to NMSC [24, 130, 131].…”
Section: Rtk Activationmentioning
confidence: 99%
“…In addition, 14-3-3ζ binding masks two nuclear localization sequences on the FOXO3a [194], which along with two already exposed nuclear export signals, induces FOXO3a cytoplasmic localization and sequestration [195]. Our lab has recently demonstrated that knockdown of either rictor or mSIN1, two key structural components of mTORC2, sensitizes keratinocytes to UVB-induced apoptosis, and that this effect is dependent on AKT-mediated FOXO3a regulation [127]. Upon exposure to UVR, FOXO3a is shuttled out of the nucleus and sequestered into the cytoplasm.…”
Section: Rtk Activationmentioning
confidence: 99%
“…Akt and 14-3-3 proteins not only repress the apoptotic roles of PACS-2 but also regulate other proapoptotic proteins, including the Bcl-2 protein Bad and FOXO transcription factors (Datta et al, 1997(Datta et al, , 2002Brunet et al, 1999;Singh et al, 2010;Feehan and Shantz, 2016). The regulation of Bad and FOXO proteins by Akt and 14-3-3 is akin to a simple molecular 'on or off' switch .…”
Section: Introductionmentioning
confidence: 99%
“…mTOR oversees pathways of cell death through apoptosis and autophagy, two mechanisms that can determine cell survival through programmed cell death (105, 130, 131) (Table 1). Apoptosis results in the activation of nucleases and proteases involving caspases (132).…”
Section: Targeting Cell Death Through Mtormentioning
confidence: 99%
“…Loss of mTOR activity (105) or components of this pathway, such as mTORC2, can result in apoptotic cell death (130). Activation of either mTOR or downstream pathways that involve p70S6K can protect against Aβ toxicity (21, 25, 97, 117, 145148), cerebral ischemia (149, 150), and oxidative stress exposure (151, 152).…”
Section: Targeting Cell Death Through Mtormentioning
confidence: 99%